2003
DOI: 10.1101/gad.1144403
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical assembly of the budding yeast kinetochore from multiple subcomplexes

Abstract: Kinetochores are multiprotein complexes that assemble on centromeric DNA and attach chromosomes to spindle microtubules. Over the past six years, the number of proteins known to localize to the Saccharomyces cerevisiae kinetochore has increased from around 10 to over 60. However, relatively little is known about the protein-protein interactions that mediate kinetochore assembly or about the overall structure of microtubule-attachment sites. Here we used biophysical techniques, affinity purification, mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
323
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(354 citation statements)
references
References 55 publications
29
323
1
1
Order By: Relevance
“…NMS group proteins reassemble to the kinetochore during prophase and toward metaphase in meiosis, and subsequently DASH group proteins localize at the centromere during chromosome segregation. These groupings are generally consistent with the complex structures revealed by genetic interactions and proteomic analyses (De Wulf et al, 2003;Cheeseman et al, 2004;Obuse et al, 2004;Liu et al, 2005).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…NMS group proteins reassemble to the kinetochore during prophase and toward metaphase in meiosis, and subsequently DASH group proteins localize at the centromere during chromosome segregation. These groupings are generally consistent with the complex structures revealed by genetic interactions and proteomic analyses (De Wulf et al, 2003;Cheeseman et al, 2004;Obuse et al, 2004;Liu et al, 2005).…”
Section: Discussionsupporting
confidence: 66%
“…Biochemical analyses have revealed that the kinetochore complex is comprised of subcomplexes of proteins. Many of these proteins are conserved in other eukaryotes, from yeasts to humans (De Wulf et al, 2003;Nekrasov et al, 2003;Cheeseman et al, 2004;Obuse et al, 2004;reviewed in Meraldi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol used for chromatin immunoprecipitation analysis was performed as described previously (De Wulf et al, 2003). Cells containing temperature-sensitive alleles were grown to log phase at 25°C, shifted to 37°C for 5 h, and fixed in 1% formaldehyde for 15 min.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…In order to get further insights into the putative involvement of Ber1 in kinetochore function, the ber1 mutant was crossed with temperature-sensitive mutants of the following essential components of the kinetochore: the aurora kinase Ipl1 (Chan and Botstein 1993), which regulates microtubule-kinetochore attachment (Buvelot et al 2003); Nnf1, a component of the central MIND kinetochore complex that contributes to linking the inner and outer kinetochore layers (De Wulf et al 2003); Ndc10 (Goh and Kilmartin 1993), which is a key component of the inner kinetochore that is necessary for kinetochore assembly (Espelin et al 2003); and Cse4 (Stoler et al 1995), a centromere-speciWc histone variant involved in kinetochore assembly (Meluh et al 1998). Altogether, these proteins are quite representative of the diVerent components of the kinetochore.…”
Section: Conwrmation Of the Involvement Of Ber1 In Kinetochore Functionmentioning
confidence: 99%